Paradigma Baru Pemikiran Dakwah Islam - Ahmad Sarbini (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2010)
In da’wah perspective, the efforts to do social transformationis not enough only rely on conventional paradigm. In its reality, the paradigm have minus attention to develop consciousness by society and tend doing exploitation to da’i interest that da’i position kineer keen da’i delighted in, the greater great its advantages only for da’i not for umat. This paradigm must be changed by placement da’i as facilitator for axchanging and supported by movement pattern that combine appreciation and emforcing vis a vis between Islamic value and cultural values and wary increasion of world isme that continuing dynamic process.